Gastrostomy Tube Placement by Radiological versus Endoscopic Methods in an Acute Care Setting: A Retrospective Review of Frequency, Indications, Complications and Outcomes. (2009) - Galaski, Amy; Peng, Wei Wei; Ellis, Michelle; Darling, Pauline; Common, Andrew; Tucker, Emma
Abstract : OBJECTIVES: To describe the current practice of placing gastrostomy tubes (endoscopic and radiological), patient characteristics, indications for enteral support, complications and outcomes over a 13-month period, and explore factors that influenced complications and outcomes. Second, to provide Canadian data regarding feeding tube placement because no current literature reflecting these practices for Canadian hospitals is available. METHODS: Retrospective chart reviews were conducted. Patients who had initial percutaneous endoscopic gastrostomy (PEG) or percutaneous radiological gastrostomy (PRG) tubes inserted for nutritional purposes were included in the study. RESULTS: A total of 136 charts which included 30 PEG and 44 PRG procedures were reviewed. The PRG group was older than the PEG group (mean [± SD] age 68±19 years versus 55±21 years, respectively; P=0.008). Patients in PEG group had longer lengths of hospital stay and more intensive care unit admissions than the PRG group (P=0.029). The main reason for tube insertion was dysphagia/aspiration (PEG [60%] and PRG [77%]). Minor complications were comparable between the two groups (P=0.678). There were three cases of major complications overall. More subjects in the PRG group died (18%) while in hospital than in the PEG group (3%) (P=0.055). No procedure-related deaths occured in either group. CONCLUSIONS: Both methods of tube insertion provided a safe route for nutrition delivery despite a significant cost differential with PEGs costing 44% more than PRGs. Characteristics such as age, presence of ascites and severity of disease influenced the method of insertion despite the lack of current guidelines. Overall, the present study provides new descriptive data in a Canadian context.